Research design : qualitative, quantitative, and mixed methods approaches - Creswell, John W. (Thousand Oaks : SAGE Publications, 2014)
This book advances a framework, a process, and compositional approaches for designing a proposal for qualitative, quantitative, and mixed methods research in the human and social sciences.
Includes index.
Includes bibliographical references, p. 251-260.
ne 19/05/2021
Loan
Keywords: Social sciences--Research--Methodology; Social sciences--Statistical methods